Comparison of selective and non‐selective internal iliac artery embolization for abnormal placentation with major postpartum hemorrhage. Issue 1 (24th October 2016) - Lo, Tsz‐Kin; So, Chun‐Hong; Yeung, Sik‐Wing; Fung, Mimi; Lui, Kwai‐Ying; Pan, Nin‐Yuan
Abstract : Non‐selective internal iliac artery embolization for abnormal placentation and postpartum hemorrhage resulted in ischemic skin necrosis whereas selective embolization did not; unilateral embolization was ineffective.